LINGUADIDACTIC BASIS OF GENERAL BODY LANGUAGE (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In English teaching, with the constant reform of teaching methods, body language as a kind of nonverbal language plays a very significant role in the interaction between teachers and students. It not only can express the speakers’ intention more accurately and effectively, simplify the teaching instruction, stimulate the students’ interest, optimize the purpose of English teaching and enhance teaching effectiveness, but also can help improve the students’ ability of listening, speaking, reading and so on. This paper aims at helping English teachers understand the application of body language in teaching, and encouraging them to try using body language in classes in order to assist their teaching. The English teachers in new times should use body language properly in their class teaching and bring its function in language teaching into full play to achieve the best teaching effects.